Cancer chemoprevention by dietary chlorophylls: A 12,000-animal dose-dose matrix biomarker and tumor study - McQuistan, Tammie J. (2011)
Recent pilot studies found natural chlorophyll (Chl) to inhibit carcinogen uptake and tumorigenesis in rodent and fish models, and to alter uptake and biodistribution of trace (14)C-aflatoxin B1 in human volunteers. The present study extends these promising findings, using a dose-dose matrix design to examine Chl-mediated effects on dibenzo(def,p)chrysene (DBC)-induced DNA adduct formation, tumor incidence, tumor multiplicity, and changes in gene regulation in the trout. The dose-dose matrix design employed an initial 12,360 rainbow trout, which were treated with 0–4000 ppm dietary Chl along with 0 – 225 ppm DBC for up to 4 weeks. Dietary DBC was found to induce dose-responsive changes in gene expression that were abolished by Chl co-treatment, whereas Chl alone had no effect on the same genes. Chl co-treatment provided a dose-responsive reduction in total DBC-DNA adducts without altering relative adduct intensities along the chromatographic profile. In animals receiving DBC alone, liver tumor incidence (as logit) and tumor multiplicity were linear in DBC dose (as log) up to their maximum-effect dose, and declined thereafter. Chl co-treatment substantially inhibited incidence and multiplicity at DBC doses up to their maximum-effect dose. These results show that Chl concentrations encountered in Chl-rich green vegetables can provide substantial cancer chemoprotection, and suggest that they do so by reducing carcinogen bioavailability. However, at DBC doses above the optima, Chl co-treatments failed to inhibit tumor incidence and significantly enhanced multiplicity. This finding questions the human relevance of chemoprevention studies carried out at high carcinogen doses that are not proven to lie within a linear, or at least monotonic, endpoint dose-response range.